2009
DOI: 10.2215/cjn.02950509
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Icodextrin versus Glucose Containing Peritoneal Dialysis Fluid

Abstract: Background and objectives: While peritoneal dialysis with icodextrin is commonly used in patients with poor peritoneal membrane characteristics, the data on the usefulness of this solution in patients with lower transport characteristics are limited. The study was designed to compare icodextrin to glucose in Chinese prevalent peritoneal dialysis patients of different peritoneal transport characteristics (PET) categories.Design, setting, participants, & measurements: This was a randomized, double-blind, perspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 18 publications
4
53
1
1
Order By: Relevance
“…It is becoming increasingly clear that one of the primary responsibilities of clinicians in the management of PD patients is the balance between adequate control of fluid status and preservation of residual renal function. Numerous clinical studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) and more than 9 years of post-marketing surveillance have confirmed that icodextrin is a safe and well-tolerated osmotic alternative PD solution to glucose. The most significant adverse effect reported to date is a cutaneous hypersensitivity reaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming increasingly clear that one of the primary responsibilities of clinicians in the management of PD patients is the balance between adequate control of fluid status and preservation of residual renal function. Numerous clinical studies (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(35)(36)(37) and more than 9 years of post-marketing surveillance have confirmed that icodextrin is a safe and well-tolerated osmotic alternative PD solution to glucose. The most significant adverse effect reported to date is a cutaneous hypersensitivity reaction (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Four studies had different dwell times in peritoneal cavity (8-16 h), which could impact the plasma glucose too. The patients in the studies by Lin et al, 3 Paniagua et al, 14 and Bredie et al 17 were in CAPD, and the patients in the study by Posthuma et al 9 were in CCPD. But, even though we excluded the study by Posthuma 9 in which the patients were in CCPD, there was no significant difference in fasting plasma glucose between the two groups.…”
Section: Discussionmentioning
confidence: 96%
“…18 High glucose concentration solutions could cause insulin resistance and dyslipidemia, which were extremely common in PD patients, and potentially had an impact on cardiovascular outcome. 19 Many studies 3,16,17,20 demonstrated that the ICO could improve the lipid metabolism. In our meta-analysis, we found that the ICO did not have statistically significantly lower blood triglycerides than the GLU, but had the different conclusion in blood total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent randomized, double-blind study from China in 201 prevalent CAPD patients compared the effect of either 7.5% icodextrin or 2.5% glucose solution for 4 weeks and reported improved small solute clearance and better UF with icodextrin. Interestingly, the increase in UF occurred across all PET transport groups, indicating that icodextrin can also be used in patients with fluid overload who have low or low-average transport status [41]. …”
Section: Novel Pd Solutions In Clinical Studiesmentioning
confidence: 99%